Pengaruh Servant Leadership Style dan Komunikasi Interpersonal Terhadap Motivasi Kerja Pegawai - Dewi Santika; Andry Stepahnie Titing; Hendrik (Journal of Trends Economics and Accounting Research, 2023)
This study aims to determine: (1) The Effect of Servant Leadership Style on Work Motivation of Environmental Service Employees of Kolaka Regency and (2) The Effect of Interpersonal Communication on Work Motivation of Environmental Service Employees of Kolaka Regency. This research uses quantitative methods. Data collection in this research used observation, literature study and distribution of questionnaires. The population in this study were non ASN employees at the Kolaka Regency Environmental Service with a total sample of 46 respondents using a purposive sampling method. Testing research instruments using validity and reliability tests with SPSS 26. Research data analysis techniques using the Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with Measurement model testing (outer model), structural model testing (inner model) and second orders with SmartPLS 4.0. Based on the research results it is known that Servant Leadership Style has a positive and significant effect on work motivation. This is evidenced by the t-count or t-statistic, which is 1,843, which is higher than the t-table value, which is >1.64. with P-values ​​of 0.033. Meanwhile, interpersonal communication also has a positive and significant effect on work motivation because the t-count or t-statistic value is 2,875 which is higher than the t-table value >1.64 with P-values ​​of 0.002. So Servant Leadership Style and Interpersonal Communication have a positive and significant effect on work motivation of 52.3%.